ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRICE EARNING RATIO (PER) PADA SAHAM PERUSAHAAN-PERUSAHAAN DI SEKTOR PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - , Redhoferri Irawan ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Stock valuation is a very important factor among others in the investment of stock. One of analysis methods most frequentlyly used is Price Earning Ratio (PER) approach. Price Earning Ratio (PER) formulated from price of stock divided by Earning per Share. By using Price Earning Ratio (PER), We could determine whether a stock is valuable to buy or not. In this thesis research will be conducted to see some of the factors that affect the value of a Price Earning Ratio (PER) for the stock of companies in the property and real estate industry listed in the Indonesian Stock Exchange (IDX). Variables which are used as independent variables are inflation rate, Return on Equity (ROE), Debt to Equity Ratio (DER), Total Assets, Sales and Spot Prices of Crude Oil and also Price Earning Ratio (PER) as the dependent variable in this study . The selection of those variables was based on several theories and research that have been done previously. Multiple regression in this study has found that 3 (three) variables from 6 (six) independent variables affect significantly to the dependent variable, Price Earning Ratio (PER). These variables are Inflation Rate, Return on Equity (ROE) and Spot Prices of Crude Oil.